Environmental and sustainable development through forestry and other resources - Banerjee, Arnab (Professor of environmental science); Jhariya, Manoj Kumar; Yadav, Dhiraj Kumar; Raj, Abhishek (Oakville, ON, Canada ; Palm Bay, Florida, USA : Apple Academic Press, 2020)
"This book, Environmental and Sustainable Development Through Forestry and Other Resources, looks at using forestry and several other innovative measures to facilitate environmental sustainability. The volume covers an important selection of research that focuses on scientific applications and trends that aim toward enhancing sustainable development in the environment. Chapters discuss such diverse topics as using agroforestry for resource management, employing legumes in agroforestry, livestock management for climate change mitigation, introducing higher plants for air pollution mitigation in urban industrial areas, the uses and benefits of sludge, technological assessment of sewage treatment plants, and much more. This book will be a helpful and informative reference for the those in the disciplines of forestry, agriculture, ecology, and environmental science and will also be a pathway to addressing new concepts for a sustainable world."--
Forests for resource management and environmental protection / Abhishek Raj, M.K. Jhariya, D.K. Yadav, and A. Banerjee -- Agroforestry systems in the hills and their ecosystem services / Abhishek Raj, M.K. Jhariya, D.K. Yadav, and A. Banerjee -- Multifunctional role of legumes in agroforestry / Abhishek Raj, M.K. Jhariya, A. Banerjee, and D.K. Yadav -- Multifunctional pastures for livestock management and climate change mitigation / Abhishek Raj, M.K. Jhariya, D.K. Yadav, and A. Banerjee -- Role of higher plants for air pollution mitigation in urban industrial areas / Shiboram Banerjee and Debnath Palit -- The uses and benefits of sludge and ways to protect against its probable harmful effects / Nazir Hussain -- Contributions of pit lakes to the socioeconomic status : a case study of the Raniganj Coal Field Area / Debnath Palit and Anjan Ray Chaudhury -- Chlorine status and drinking water quality monitoring within a public distribution system of Kollam District / Anila George -- Effect of environmental pollution on health and its prevention : an overview / Pallavi Chattopadhyay, Pinaki Chattopadhyay, and Debnath Palit -- Innovative approach to sustainable development and biodiversity conservation / Pinaki Chattopadhyay, Pallavi Chattopadhyay, and Debnath Palit -- Prospects of biotechnology for a sustainable environment / Saikat Mondal and Debnath Palit -- Technological assessment of sewage treatment plants / Harshita Jain, Renu Dhupper, Vishal Gandhi, and Geetanjali Kaushik.
OCLC-licensed vendor bibliographic record.
Keywords: Sustainable forestry; Sustainable development; NATURE / Environmental Conservation & Protection; SCIENCE / General; SCIENCE / Environmental Science